2021
DOI: 10.1136/bcr-2021-243829
|View full text |Cite
|
Sign up to set email alerts
|

Sequential contralateral facial nerve palsies following COVID-19 vaccination first and second doses

Abstract: A 61-year-old man presented to the ENT emergency clinic with a history of unilateral facial nerve palsy occurring shortly after each dose of the Pfizer-BioNTech COVID-19 vaccine. The first episode developed 5 hours after administration of the first dose and the second 2 days after administration of the second dose. Investigations at initial presentation to the emergency department were unremarkable, and the patient was diagnosed with Bell’s palsy on both occasions. We describe the first case of Bell’s palsy oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…We can assume that the timing of Bell's palsy onset after mRNA vaccine administration varies, with early manifestation occurring as early as 5 h after vaccination, as reported in a male patient who received BNT162b2 and developed recurrent Bell's palsy after the second dose of vaccine. 8 In this case, the first episode occurred 5 h after the first dose was administered, and the second occurred 2 days later.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We can assume that the timing of Bell's palsy onset after mRNA vaccine administration varies, with early manifestation occurring as early as 5 h after vaccination, as reported in a male patient who received BNT162b2 and developed recurrent Bell's palsy after the second dose of vaccine. 8 In this case, the first episode occurred 5 h after the first dose was administered, and the second occurred 2 days later.…”
Section: Discussionmentioning
confidence: 81%
“…, 7. , 8. ; a recent study analyzed the reported frequency of neuralgic amyotrophy, Bell's palsy, and Guillain-Barrè syndrome in VigiBase, the World Health Organization's (WHO) global database of suspected adverse drug reactions, in patients who received COVID-vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cases are reported of peripheral facial palsy after immunization with PBV: a patient with two episodes of contralateral Bell's palsies arising shortly after inoculation with the first and second dose of the PBV 5 and other cases of unilateral facial palsy occurring 36 h after the second dose. 6 Another published case involved abducens nerve palsy 2 day after PBV.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of Bell’s palsy have been reported after receipt of either the BNT162b2 or mRNA-1273 vaccine. [22,28,29] Furthermore, the estimated rate ratio of Bell’s palsy among participants of BNT162b2 and mRNA-1273 clinical trials assigned to the vaccine group versus those receiving placebo was 7.0 (p=0.07), suggesting a strong association. [17] Similarly, we observed an increased frequency of Bell’s palsy and some of its symptoms, such as facial paralysis and dysgeusia,[30] after BNT162b2 vaccination.…”
Section: Discussionmentioning
confidence: 99%